ANALISIS PELAKSANAAN KEGIATAN PEMBELAJARAN JARAK JAUH DITINJAU DALAM PERSPEKTIF PENILAIAN AUTENTIK - Sakura Agnestia, Rifany; Adya Pribadi, Reksa; Nur Rasya Ramadhan, Siti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
The purposes of this study were to understand how effective distance learning in elementary school and how to discover the results of distance learning in authentic assessment perspective at SDIF Al - Fikri Sukmajaya District, Depok City, West Java.The subjects of the study were the first grade students of SDIF Al-Fikri for the academic year 2020/2021, with a total of 10 students, consisted of 6 female students and 4 male students. The first cycle consisted of 1 (one) meeting and the second cycle consisted of 3 (three) meetings, with the research procedures including: interviews and observations. The results demonstrated that the analysis of the implementation of distance learning activities was effective at SDIF Al - Fikri because the teachers and staff carried out learning according to the needs of students thus authentic assessments did not disappear during the implementation of distance learning.